Exploring respectful maternity care during pregnancy and childbirth: A mothers’ and birthing persons’ perspective following a UK hospital birth - Edwards-Bailey, Laura (2024)
Background Childbirth is a significant life-event; however, approximately 45.5% of global births are experienced as traumatic by mothers/birthing people. To promote positive and empowering births, the World Health Organisation published the model of Intrapartum Care in 2018. Delivery of Respectful Maternity Care (RMC) and establishing Psychologically Safe Environments were proposed. However, understanding of these concepts is limited, calling for further research with birthing people to “describe their vision for respectful care and experiences”. Literature exploring birthing experiences is often limited to homogeneous samples of white middle-class mothers despite worse birthing outcomes for ethnic minorities and those from lower socioeconomic backgrounds; and focuses specifically on birth rather than the whole pregnancy experience. Considering this alongside recent reports of unsafe care, lacking respect, kindness and compassion in UK maternity services, this study aimed to explore the meaning of RMC and psychological safety amongst a heterogeneous sample of mothers/birthing people.